(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
The optimum utilization of the renewable energy potential is one of the priorities of the Bulgarian economy and energetic. Investors and engineers increasingly often face questions connected with taking the best solutions concerning solar thermal systems, solar yield and the quantity of delivered energy. World market offers a great number of simulation programs for solar thermal energy assessment: yield prognosticating ones, others for solar thermal system sizing, process optimization, etc. A comparative analysis has been made in the present study of the stimulation programs for solar thermal systems. A classification is suggested according to the process of programming and examination made of models representing the classification. Each of the instruments is described in short together with an account of its good and weak points. A table presents information for the different model comparison based on users‟ necessary qualification, number of program users, users‟ category, the computer platforms needed, program language, prices, etc. The information presented can serve a substantial advantage for engineers, constructors, university lecturers and students working in the field of RES.